Evaluation of the Association of Alveolar Bone Dimensions in Unilateral Palatally Impacted Canine: A Cone-Beam Computed Tomography Analysis - Amir Hooman Sadrhaghighi; Sajad Farrokhi; Maryam Rad; Mahsa Eskandarinezhad (Wolters Kluwer Medknow Publications, 2022)
Introduction: Maxillary canine impaction is directly associated with changes in dentoalveolar dimensions and adjacent teeth displacement. This investigation aimed to perform skeletal and dentoalveolar measurements of unilateral palatally impacted canines and compare them with the unaffected contralateral side using cone-beam computed tomography (CBCT). Materials and Methods: This cross-sectional study examined unilaterally impacted canines of the maxilla in 46 CBCT scans. The lateral incisor angulations, nasal cavity width, alveolar bone height, bucco-palatal width, and arch perimeter were measured and compared on both impaction and unaffected sides. All statistical tests were two-sided and analyzed using the paired sample t test and the Kolmogorov-Smirnov test using SPSS 26.0. A P < 0.05 was deemed statistically meaningful. Results: On the impacted side, a significant decrease was observed in the width of the alveolar bone at the height of 2 mm (P = 0.001). Furthermore, at the height of 10 mm, the impacted side was significantly thicker (P = 0.001). There was a statistically significant difference between the maxillary arch width on the nonimpacted and impacted sides (P = 0.001); the distance of mid-palatine raphe to the first premolar and canine proximal bone on the non-impaction side was significantly lower (13.251 ± 1.75 mm) compared to the impacted side (14.334 ± 1.80 mm) (P = 0.01). The external angle of the lateral maxillary incisor on the impacted side (86.803 ± 8.425°) showed a significant decrease (P = 0.001) compared with the contralateral side (91.403 ± 6.791°). Conclusion: The lateral incisors' lateral angulations, the inter-premolar width, and the alveolar bone thickness can be affected by palatally impacted canine teeth. However, the height of the alveolar bone and the width of the nasal cavity are not affected.